RLIP76: A novel glutathione-conjugate and multi-drug transporter - Singhal, Sharad S. (2008)
RLIP76, a stress-responsive, multi-functional protein with multi-specific transport activity towards glutathione-conjugates (GS-E) and chemotherapeutic agents, is frequently over-expressed in malignant cells. Our recent studies suggest that it plays a prominent anti-apoptotic role selectively in cancer cells. We have previously shown that RLIP76 accounts for up to 80% of the transport of GS-E and blocking the RLIP76-mediated transport of GS-E in cells results in the accumulation of pro-apoptotic endogenous electrophiles and on-set of apoptosis. Here we demonstrate that when RLIP76 mediate transport of GS-E is abrogated either by anti-RLIP76 IgG or accumulation of 4-hydroxynonenal (4-HNE) and its GSH-conjugate (GS-HNE) occurs and a massive apoptosis is observed in cells, indicate that the inhibition of RLIP76 transport activity at the cell surface is sufficient for observed anti-tumor activity. RLIP76 is linked with certain cellular functions including membrane plasticity and movement (as a primary `effector' in the Ral pathway, perhaps functioning as a GTPase activating protein, or GAP), and as a component of clathrin-coated pit-mediated receptor-ligand endocytosis—a process that mediates movement of membrane vesicles.